Short‐ and long‐term clinical predictors of pharmacological cardioversion of persistent atrial fibrillation by dofetilide: A retrospective cohort study of 160 patients. Issue 7 (14th March 2017) - Hassan Virk, Hafeez Ul; Qureshi, Waqas T.; Makkar, Nayani; Bastawrose, Joseph; Souvaliotis, Nektarios; Aziz, Joshua; Aziz, Emad
Abstract : Introduction: Dofetilide is a class III antiarrhythmic prescribed to cardiovert persistent atrial fibrillation (AF) to sinus rhythm (SR). Hypothesis: To determine the clinical predictors of cardioversion and readmission in persistent AF patients on dofetilide. Methods: We analyzed 160 patients with persistent AF who were started on dofetilide and followed for 1 year. We examined age, sex, race, hypertension, diabetes, smoking, dyslipidemia, CAD, left ventricular ejection fraction (LVEF), creatinine, BMI and concomitant use of calcium channel blockers (CCB), β‐blockers in a multivariable logistic regression model. We also examined the same predictors in Cox regression model for AF‐related readmission within 1 year of follow‐up. Results: 13.5% individuals did not convert to SR on dofetilide. 55.6% converted on the first dose and 83.1% converted by the fourth dose. In multivariable logistic models, dyslipidemia (OR: 2.4, CI: 1.12‐5.16) and LVEF (OR: 3.83, CI: 1.37‐10.8) were associated with failure to convert with the first dose. Female sex and LVEF also were associated with increased risk of failure to convert at all. Concomitant use of CCB associated with decreased risk of failure to convert to SR. In Cox proportional model, female sex, age <63 years and CAD were associated with increased AF readmission within 1 year. Conclusions: Dyslipidemia and LVEF <40% were associated with failure to cardiovert after first dose, and female sex and LVEF 40% were related to failure to convert at all on dofetilide in persistent AF patients. After 1‐year follow‐up, female sex, known CAD, and age <63 years were associated with increased AF readmissions.